Open and Standardized Resources for Smart Transducer Networking - Rossi, Silvano R.; Carvalho, Aparecido A. de [UNESP]; Silva, Alexandre César Rodrigues da [UNESP]; Batista, Edson A.; Kitano, Claudio [UNESP]; Santos Filho, Tercio A. [UNESP]; Prado, Thiago A. (Institute of Electrical and Electronics Engineers (IEEE), 2009)
IEEE 1451 standard is intended to address the smart transducer interfacing problem in network environments. Usually, proprietary hardware and software are a very efficient solution for implementing the aforementioned normative, although they can become expensive and inflexible. In contrast, the use of open and standardized resources for implementing the IEEE 1451 smart transducer interface standards is proposed in this paper. Tools such as Java and Phyton programming languages, Linux, low-cost programmable logic devices, personal computer resources, and Ethernet architecture were integrated to construct a network node based on the IEEE 1451 standard. The node can be used in systems based on the client-server communication model. The evaluation of the employed tools and experimental results are presented.
Keywords: IEEE 1451; interface; network; open and standardized resources; smart transducer